Effect of different angle scanning on density estimation based on Hounsfield Unit on CT and CBCT - Maya Genisa,; Zainul Ahmad Rajion,; Dasmawati Mohamad,; Abdullah Pohchi,; Mohd Rafiq Abdul Kadir,; Solehuddin Shuib, (Universiti Kebangsaan Malaysia, 2015)
This study aim to evaluate the effect of different angle on bone density estimation based on HU on CT and CBCT scanning. A phantom of jaw was scanned using CT and CBCT machine from different angle (0, 15 and 30 degrees). The data were transformed into DICOM format and loaded into MIMICS software for density measurement. The density was measured at 9.55 mm from cemento-enamel junction (CEJ) on every different angle scanning data. Then these data were grouped as Group A1, A2 and A3 for CBCT group (0, 15 and 30 degrees, respectively) and Group B1, B2 and B3 for CT group (0, 15 and 30 degrees, respectively). The differences between the groups and the references (0 degree scanning) are measured statistically using SPSS software. In the CBCT data, the density reading at 15 and 30 degrees are higher than 0 degree scanning (mean difference = -155.63±62.61, p=0.03, mean difference = -33.13±84.24, p=0.206 for 15 and 30 degrees scanning, respectively). In the CT data, the density at 15 and 30 degrees scanning is lower than at 0 degrees scanning (mean different: 84.49±46.76, p=0.09 and 15.09±23.61, p=0.532). The differences are not significant statistically. Compared with CT, the effect of different angle scanning on density estimation on CBCT is stronger. These results showed that different angle scanning produce more error on density estimation based on HU on CBCT compared with CT. This study demonstrated that the uses of a CBCT and CT for density monitoring to evaluate bone density of jaws are affected by angle scanning.